Application and underlying mechanism of acupuncture for the nerve repair after peripheral nerve injury: remodeling of nerve system - Yang, Yongke; Rao, Chang; Yin, Tianlong; Wang, Shaokang; Shi, Huiyan; Yan, Xin; Zhang, Lili; Meng, Xianggang; Gu, Wenlong; Du, Yuzheng; Hong, Feng (Frontiers in Cellular Neuroscience, 2023)
Peripheral nerve injury (PNI) is a structural event with harmful consequences worldwide. Due to the limited intrinsic regenerative capacity of the peripheral nerve in adults, neural restoration after PNI is difficult. Neurological remodeling has a crucial effect on the repair of the form and function during the regeneration of the peripheral nerve after the peripheral nerve is injured. Several studies have demonstrated that acupuncture is effective for PNI-induced neurologic deficits, and the potential mechanisms responsible for its effects involve the nervous system remodeling in the process of nerve repair. Moreover, acupuncture promotes neural regeneration and axon sprouting by activating related neurotrophins retrograde transport, such as nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), glial cell-derived neurotrophic factor (GDNF), N-cadherin, and MicroRNAs. Peripheral nerve injury enhances the perceptual response of the central nervous system to pain, causing central sensitization and accelerating neuronal cell apoptosis. Together with this, the remodeling of synaptic transmission function would worsen pain discomfort.Neuroimaging studies have shown remodeling changes in both grey and white matter after peripheral nerve injury. Acupuncture not only reverses the poor remodeling of the nervous system but also stimulates the release of neurotrophic substances such as nerve growth factors in the nervous system to ameliorate pain and promote the regeneration and repair of nerve fibers. In conclusion, the neurological remodeling at the peripheral and central levels in the process of acupuncture treatment accelerates nerve regeneration and repair. These findings provide novel insights enabling the clinical application of acupuncture in the treatment of PNI.